Amyophatic dermatomyositis presenting as a flagellated skin eruption with positive MDA5 antibodies and thyroid cancer: a real association?. (9th May 2015) - Molina‐Ruiz, A. M.; Romero, F.; Carrasco, L.; Feltes, F.; Haro, R.; Requena, L.
Summary: Amyopathic dermatomyositis (ADM) is characterized clinically by typical skin lesions with hypomyopathy or no muscular involvement. ADM has been recently reported to be complicated by rapidly progressive interstitial lung disease (ILD), especially in patients with positive antibodies against melanoma differentiation‐associated gene 5 ( MDA5 ). These patients may have a low risk of cancer, but no clinical, histological or laboratory markers completely specific for paraneoplastic DM have been identified to date. We report a case of flagellate erythema as the initial presentation of ADM associated with ILD, positive MDA5 antibodies and a concomitant diagnosis of thyroid cancer. We discuss the unusual clinical features and associations that make this case particularly interesting.